2018
DOI: 10.1038/s41380-018-0285-0
|View full text |Cite
|
Sign up to set email alerts
|

CircDYM ameliorates depressive-like behavior by targeting miR-9 to regulate microglial activation via HSP90 ubiquitination

Abstract: Circular RNAs (circRNAs), highly expressed in the central nervous system, are involved in various regulatory processes and implicated in some pathophysiology. However, the potential role of circRNAs in psychiatric diseases, particularly major depressive disorder (MDD), remains largely unknown. Here, we demonstrated that circular RNA DYM (circDYM) levels were significantly decreased both in the peripheral blood of patients with MDD and in the two depressive-like mouse models: the chronic unpredictable stress (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 61 publications
2
90
2
1
Order By: Relevance
“…MiR-124 and −132 are mostly restricted to the nervous system and are key to brain development through their roles in neuronal differentiation (miR-124) [61] and morphogenesis (miR-132) [62]. MiR-9 regulates microglia function through its target HECT domain E3 ubiquitin protein ligase 1 (HECTD1) [63] and miR-29a has been implicated in apoptotic pathways following endoplasmic reticulum stress via its target, an apoptosis regulator: myeloid leukemia cell differentiation protein (Mcl-1) [64]. In addition, RE1 silencing transcription factor (REST), a transcription factor involved in neuronal differentiation, was upregulated after maternal separation [52].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…MiR-124 and −132 are mostly restricted to the nervous system and are key to brain development through their roles in neuronal differentiation (miR-124) [61] and morphogenesis (miR-132) [62]. MiR-9 regulates microglia function through its target HECT domain E3 ubiquitin protein ligase 1 (HECTD1) [63] and miR-29a has been implicated in apoptotic pathways following endoplasmic reticulum stress via its target, an apoptosis regulator: myeloid leukemia cell differentiation protein (Mcl-1) [64]. In addition, RE1 silencing transcription factor (REST), a transcription factor involved in neuronal differentiation, was upregulated after maternal separation [52].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Moreover, recent studies utilized novel circRNA annotation approaches to extract circRNA expression data from RNAsequencing experiments in the dorsolateral prefrontal cortex (DLPFC) of subjects with SCZ [27,28]. Furthermore, another study uncovered alterations in a circRNA altered in the blood of patients with monopolar depression that could regulate microglial activation and depressive-like behavior in mice, thus highlighting the role of circRNAs in glial function [29]. However, nothing is known thus far about the importance of neuronal-enriched circRNAs with direct relevance to SCZ and BD in neuronal gene expression and disease-related cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Most circRNAs are composed of exon sequences of protein-coding genes and are highly conserved in different species, although some are also derived from intronic, intergenic, and untranslated regions. Recent studies showed that circRNAs expressing in the cytoplasm of mammal cells could act as microRNA (miRNA) sponges to block the effect of miRNA on target messenger RNA (mRNA) and regulate disease processes such as depression, stroke, and cancer (14)(15)(16). Our previous studies showed that circDYM ameliorates depressive-like behaviors by targeting miR-9 to regulate microglial activation via HSP90 ubiquitination (15) using high-throughput sequencing and found that circRNA-mm9_circ_0015149, known as circSTAG1, was downregulated in chronic unpredictable stress (CUS)-treated mice (GEO accession number: GSE135343).…”
mentioning
confidence: 99%